Regional Resources Capitalization: Theoretical and Methodological Basis - Lyshchikova, Julia V.; Orlova, Anna V.; Nikulina, Yevgenia V.; Anokhin, Yevgeny I. (International Journal of Economics and Financial Issues, 2016)
The article substantiates the holistic theoretical approach to the definition of the economic content, dominant characteristics, the structure and features of the regional resource potential as the basis of the regional economy capitalization. The methodological platform, an updated and expanded conceptual and categorical apparatus of capitalization of the regional economy is presented in the paper. The authors conducted identification, classification and structural-functional decomposition of the elements of the resource potential, objectives, subjects, objects and mechanisms of capitalization of the territory taking into account the differentiation of their role, scale and impact on the process. Keywords: capitalization, regional economy, regional resource potential, methodological platform, capitalization mechanisms JEL Classifcations: E22, O16, O18, P48